Why crying does and sometimes does not seem to alleviate mood: a quasi-experimental study - Gračanin, Asmir (Motiv Emot, 2015)
Whereas retrospective studies suggest that crying can be beneficial in terms of mood enhancement, results of quasi-experimental laboratory studies consistently demonstrate its negative effects on mood. The present study was specifically designed to evaluate a parsimonious explanation for this paradox by assessing mood after crying in a laboratory, both immediately and at follow up. Mood ratings of 28 objectively established criers and 32 non-criers were compared before and immediately after the exposure to an emotional movie, as well as 20 and 90 min later. As expected, immediately after the film, negative mood significantly increased in criers, while it did not change in non-criers. This mood deterioration was followed by a recovery that resulted in return to the baseline mood levels at the third measurement. Criers subsequently reported mood enhancements at the final measurement compared to the pre-film measurement. Crying frequency did not predict mood changes above those predicted by the presence of crying. The observed relation between crying and more long-term mood recovery reconciles seemingly contrasting earlier results and provides a simple and obvious explanation. After the initial deterioration of mood following crying that was observed in laboratory studies, it apparently takes some time for the mood, not just to recover, but also to become even less negative than before the emotional event, which corresponds to the results of retrospective studies.